Assay and Inhibition of Diacylglycerol Lipase Activity - Johnston, Meghan (2012)
A series of N-formyl-α-amino acid esters of β-lactone derivatives structurally related to tetrahydrolipstatin (THL) and O-3841 were synthesized that inhibit human and murine diacylglycerol lipase (DAGL) activities. New ether lipid reporter compounds were developed for an in vitro assay to efficiently screen inhibitors of 1,2-diacyl-sn-glycerol hydrolysis and related lipase activities using fluorescence resonance energy transfer (FRET). A standardized thin layer chromatography (TLC) radioassay of diacylglycerol lipase activity utilizing the labeled endogenous substrate [1″-(14)C]1-stearoyl-2-arachidonoyl-sn-glycerol with phosphorimaging detection was used to quantify inhibition by following formation of the initial product [1″-(14)C]2-arachidonoylglycerol and further hydrolysis under the assay conditions to [1-(14)C]arachidonic acid.